Folic acid modulates VPO1 DNA methylation levels and alleviates oxidative stress-induced apoptosis in vivo and in vitro - Cui, Shanshan; Lv, Xin; Li, Wen; Li, Zhenshu; Liu, Huan; Gao, Yuxia; Huang, Guowei (Redox biology, 2018)
Endothelial cell injury and apoptosis play a primary role in the pathogenesis of atherosclerosis. Moreover, accumulating evidence indicates that oxidative injury is an important risk factor for endothelial cell damage. In addition, low folate levels are considered a contributing factor to promotion of vascular disease because of the deregulation of DNA methylation. We aimed to investigate the effects of folic acid on injuries induced by oxidative stress that occur via an epigenetic gene silencing mechanism in ApoE knockout mice fed a high-fat diet and in human umbilical vein endothelial cells treated with oxidized low-density lipoprotein (ox-LDL). We assessed how folic acid influenced the levels of 8-hydroxy-2′-deoxyguanosine (8-OHdG, an oxidative DNA damage marker) and cellular apoptosis in in vivo and in vitro models. Furthermore, we analyzed DNA methyltransferase (DNMT) activity, vascular peroxidase 1 (VPO1) expression, and promoter methylation in human umbilical vein endothelial cells. Our data showed that folic acid reduced 8-OHdG levels and decreased apoptosis in the aortic tissue of ApoE−/− mice. Likewise, our in vitro experiments showed that folic acid protects against endothelial dysfunction induced by ox-LDL by reducing reactive oxygen species (ROS)-derived oxidative injuries, 8-OHdG content, and the apoptosis ratio. Importantly, this effect was indirectly caused by increased DNMT activity and altered DNA methylation at VPO1 promoters, as well as changes in the abundance of VPO1 expression. Collectively, we conclude that folic acid supplementation may prevent oxidative stress-induced apoptosis and suppresses ROS levels through downregulating VPO1 as a consequence of changes in DNA methylation, which may contribute to beneficial effects on endothelial function. [Display omitted] •Folic acid reduces oxidative stress-induced injuries in atherosclerosis.•Folic acid decreases 8-OHdG levels and apoptosis in vivo and in vitro.•Folic acid supplementation increases DNMT levels and regulates VPO1 expression.•VPO1 expression is modulated by epigenetic silencing via promoter methylation.